2001
DOI: 10.2527/2001.7961483x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultrasound imagery and body shape to predict carcass and fillet yield in farm-raised catfish.

Abstract: Accurate prediction of meat yield in live animals may allow more efficient genetic improvement of meat yield in farm-raised catfish. An initial trial with 30 channel catfish demonstrated significant correlations among weight-adjusted residuals for muscle area measured from transverse ultrasound images and transverse sections at five locations along the trunk musculature (r = 0.30 to 0.70). Relationships of weight-adjusted residuals for three meat yield traits (carcass, whole fillet, and shank fillet) with weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 12 publications
(15 reference statements)
3
34
2
1
Order By: Relevance
“…However, fish production is heavily dependent on quick, accurate and, above all, non-invasive methods to predict carcass composition in live fish (Probert and Shannon, 2000;Veliyulin et al ., 2005;Silva et al ., 2010a). Comprehensive studies using image techniques such as CT (Romvári et al ., 2002;Hancz et al ., 2003;Kolstad et al ., 2004), MRI (Collewet et al ., 2001;Veliyulin et al ., 2005) and RTU (Bosworth et al ., 2001;Rodrigues et al ., 2010;Silva et al ., 2010a) have shown that these techniques are able to predict carcass traits in fish. From a practical point of view, CT has several characteristics that make it the preferred technique for in vivo evaluation of carcass composition in fish.…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
See 3 more Smart Citations
“…However, fish production is heavily dependent on quick, accurate and, above all, non-invasive methods to predict carcass composition in live fish (Probert and Shannon, 2000;Veliyulin et al ., 2005;Silva et al ., 2010a). Comprehensive studies using image techniques such as CT (Romvári et al ., 2002;Hancz et al ., 2003;Kolstad et al ., 2004), MRI (Collewet et al ., 2001;Veliyulin et al ., 2005) and RTU (Bosworth et al ., 2001;Rodrigues et al ., 2010;Silva et al ., 2010a) have shown that these techniques are able to predict carcass traits in fish. From a practical point of view, CT has several characteristics that make it the preferred technique for in vivo evaluation of carcass composition in fish.…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
“…(2001) reported that ultrasound measurements of muscle area in live fish are strongly correlated with the equivalent measurements take on the carcass ( r = 0.84-0.94; P < 0.001), but in meat yield measurements there was only moderate correlation between the two. A single transverse ultrasound scan accounted for 40-50% of the variation in meat yield traits in female catfish, and 16-23% in male catfish (Bosworth et al ., 2001). In the same study, using multiple regressions, Bosworth et al .…”
Section: Use Of Rtu To Predict Carcass Composition and Meat Traits Inmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, using ultrasound imaging, Bosworth et al [3] explained 48-56% and 31-38% of the variation in meat yield traits in female and male catfish, respectively. Sang et al [4] studied methods to measure quality traits of river catfish by taking measurement of the live fish.…”
Section: Methods To Measure Quality Traitsmentioning
confidence: 99%